(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2022)
A study on genetic diversity analysis was conducted on Rusa timorensis obtained from state of Perak and state of Pahang to investigate the level of genetic diversity occur and to compare the diversity amongst two R. timorensis breeders in Malaysia. A total of six (n=6) individual samples of R. timorensis were extracted from Tanjung Malim, Perak and Bilut Agro Farm, Pahang and amplified using mitochondria deoxyribonucleic acid (mtDNA) primers gene as a target molecular marker. The mtDNA region was amplified using a set of cytochrome b gene primers (5”AAACCAGAAAAGGAGAGCAAC3”;5”TCATCTAGGCATTTTCAGTGCC3”) and nucleotide sequence of the mtDNA cyt b was aligned by using MEGA Ver 7.0. The result indicated that the R. timorensis from Pahang has a low degree of variation (0.252) of genetic distance compared to, R. timorensis from Perak (0.696). The phylogenetic three analysis, indicated, R. timorensis from Pahang resulted the highest intra-specific relationship at 100% compared to , R. timorensis from Perak at 63% of intra-specific relationship. The results showed that the genetic diversity of, R. timorensis in Perak and Pahang is likely to decrease in the future. Therefore, future breeding program plan needs to be implemented to diversify the genetics of genus Rusa in Malaysia.